Biossensor enzimático baseado em peroxidase de ingá-cipó imobilizada em sepiolita para quantificação de antioxidantes em alimentos - Oliveira, Tássia Regina de (2014)
This work describes the development of a new enzymatic biosensor for the antioxidant tert-butylhydroquinone (TBHQ). Sepiolite clay mineral was used as a support for the immobilisation of the peroxidase enzyme from ingá-cipó (Inga edulis Mart.), together with graphite powder, multi-walled carbon nanotubes, mineral oil, and Nafion® 0.5% (v/v) in the construction of a biosensor. For the optimisation and application of the biosensor, several parameters were investigated to determine the optimum experimental conditions using square-wave voltammetry (SWV). The best performance was obtained using a 0.1 mol L-1 phosphate buffer solution (pH 7.0), 4.0×10-4 mol L-1 hydrogen peroxide, a frequency of 50 Hz, a pulse amplitude of 60 mV, and a scan increment of 6 mV. The biosensor showed good repeatability and intermediate precision, and remained stable for a period of 20 weeks. The analytical curve revealed a linear response range of 1.65 to 9.82 mg L-1 (r2 = 0.994) with detection and quantification limits of 0.4 and 1.2 mg L-1. A recovery study of TBHQ in salad dressing samples yielded values from 99.6–104.8%, exhibiting good accuracy. The proposed biosensor was successfully employed for the determination of TBHQ in commercial salad dressing sample, giving a relative error of 5.4% in relation to the comparative method chromatographic (liquid chromatography).